Some Uniqueness Results on Meromorphic Functions Sharing Two or Three Sets - Banerjee, Abhijit; Mukherjee, Sonali (Sarajevo Journal of Mathematics, 2024)
Using the notions of weighted and pseudo sharing of sets, we prove some uniqueness theorems on meromorphic functions that share two or three sets. The results in this paper improve and supplement many known results. 2000 Mathematics Subject Classification. 30D35